Milk Yield, Fertility, Udder Characteristics, and Raw Milk Somatic Cell Count of the Damascus Goats Reared in Iğdır Conditions - Yılmaz, İsa; Can, Ali (My University, 2022)
The aim of this study is to determine the somatic cell number (SCC), udder characteristics and some yield characteristics in Damascus goats. This study was carried out on the Damascus goats raised on a private farm brought the first time in Iğdır province of Turkey in 2013. In the study, 62 Damascus goats were measured SCC of 620 milk samples, monthly milk yields, and udder characteristics in 2019. In the study, mean values of some udder characteristics such as udder circumference, udder width, udder bottom height, udder upper height, teat angle, udder volume, teat diameter, and teat length were determined as 41.83±0.13 cm, 13.07±0.04 cm, 30.57±0.14 cm, 51.01±0.15 cm, 38.02±0.13º, 1754.84±10.65 ml, 6.09±0.09 mm and 5.44±0.06 cm, respectively. In raw milk, mean values of SCC and logarithmic Log10SCC were found as 503,120±40,020 cells ml-1 and 5,543±0.037 cells ml-1, respectively. The effect of birth type and lactation order on SCC and Log10SCC was found to be significant (p<0.01). Average daily milk yield, lactation length, and lactation milk yield, which are among the factors affecting milk yield, were found as 2.14±0.05 kg, 292.15±0.60 day, and 626.23±12.94 kg, respectively. The effect of lactation length and season on average dairy milk yield was found to be significant (p<0.01). The effects of udder type on lactation length (p<0.05), and lactation duration on lactation milk yield were found significant (p<0.01). As a result, it has been concluded that Damascus goats can be successfully raised under the conditions of Iğdır province.